Physical determinants of golf swing performance in competitive youth golfers - Shaw, J.; Gould, Z. I.; Oliver, J.; Lloyd, R. S. (Journal of Sports Sciences, 2023)
This study investigated measures of physical fitness and golf swing performance in competitive youth golfers. Sixty-four golfers, subdivided into three handicap groups (CAT0, <1 handicap, n = 21; CAT1, 1-5 handicap, n = 20; CAT2, >5 handicap, n = 23), were assessed for isometric strength, power, movement competency and core endurance. Clubhead speed (CHS) and carry distance for 6-iron and driver were also measured. When controlled for maturity offset, CAT0 golfers produced significantly greater peak power, isometric absolute and relative peak force, movement competency, and jump distance than higher handicap golfers (all p < 0.05). Maturity status was strongly associated with CHS and carry distance for both clubs (R2 = 0.552-0.784). Linear regressions showed maturity offset explained a larger amount of variance in CHS (driver = 78.4%, 6-iron = 71.3%) and carry distance (driver = 55.2%, 6-iron = 57.4%) than handicap. Multiple linear regression analyses showed that peak power explained 79.4% and 82.4% of variation in 6-iron and driver CHS, respectively, while isometric absolute peak force explained 69.6% and 74.3% of the variation in 6-iron and driver carry distance, respectively. Subsequently, interventions targeting the development of peak force and power could aid golf swing performance in young golfers.